Vested Interest In Judicial Election Reflected In John Grisham's The Appeal (2008): A Sociological Approach - Pangestiani., Brighitta Dian Pristi; , Dr. M. Thoyibi, M.S; , Siti Fatimah, S. Pd, M. Hum (2014)
This research aims at analyzing vested interestt in judicial election in John Girsham's The Appeal by using Sociological Approach. The major problem in this research is how democracy as a way to reach vested interest is reflected in John Girsham's The Appeal. The research consists of two objectives: analyzing the novel based on structural elements and analyzing the novel based on Sociological Approach. This study uses qualitative research. The object of the study is The Appeal novel written by John Girsham. There are two kinds of data source: primary and secondary. The primary data source is the text of the novel by John Grisham's The Appeal and the secondary data source are some books ad article related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer applies descriptive analysis. The results of the research are as follows. First, based on structural analysis, it is apparent that this novel contains a moral message that actually there are vested interests in all aspect of life; the upper class can set the law because the law can be purchased. Second, based on Sociological analysis, this novel describes the way justice have-on dirty trick in a judgment.